The Employee Performance Seen from the Aspects of Organizational Culture and Commitment at the Education Office of Pematangsiantar City - Novita Butarbutar; Erbin Chandra; Grace Endang Pakpahan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
The objective of this study was to determine the effect of organizational culture and commitment to employee performance at the Education Office of Pematangsiantar City. This study used literature and field research designs. The research method used was the causality method with a quantitative approach. The type of data used in this study was qualitative data and quantitative data. The data sources consisted of primary data and secondary data. The population and sample used in this study were 81 permanent employees. The data collection was carried out by questionnaire, interview and documentation. The analysis technique used was qualitative descriptive and quantitative descriptive analysis consisting of multiple linear regression, correlation test and determination and hypothesis tests. The results of this study concluded that the organizational culture, commitment and employee performance were good. Besides, the organizational culture had a positive and significant effect on employee performance. Furthermore, the commitment had a positive and significant effect on employee performance.